Increasing Regional Administrative Capacity: Effective Approaches and Strategies - Muliati; Ibrahim; Lenas, Meldilianus Nabas J (Sinergi International Journal of Management and Business, 2023)
This research discusses efforts to increase regional administrative capacity in Indonesia. The main focus is to understand various effective approaches and strategies that can be implemented to strengthen local government administration. By exploring the literature and analyzing relevant findings, this research identifies approaches such as training, community participation, partnerships, and the use of information technology and e-government. In addition, key factors influencing the success of administrative capacity building efforts, such as political support and coordination, are also discussed. This research provides valuable insights for more effective policy making in supporting sustainable regional development in Indonesia.